Patient sex does not affect endoscopic outcomes of biologicals in inflammatory bowel disease but is associated with adverse events - Lie, Mitchell R. K. L. (Int J Colorectal Dis, 2020)
PURPOSE: Biological therapies are currently the mainstay in the treatment of patients with inflammatory bowel diseases (IBD). Several factors are known to influence the efficacy and tolerability of biologicals, such as CRP levels or previous biological use. Whether patient sex affects the efficacy or tolerability is unclear but would help with better risk and benefit stratification. This systematic review assesses patient sex on the efficacy and tolerability of biological therapies in IBD patients. METHODS: A systematic literature review was performed using Embase (including MEDLINE), MEDLINE OvidSP, Cochrane Central Register of Controlled Trials, Web of Science and PubMed. The primary outcome was the influence of patient sex on endoscopic outcomes in IBD patients treated with biologicals. The secondary outcome was the influence of patient sex on adverse events. Studies were included in the assessment regardless of study type or setting. RESULTS: The search yielded 19,461 citations; after review, 55 studies were included in the study, involving 28,465 patients treated with adalimumab, certolizumab pegol, infliximab, or vedolizumab. There was no significant association between patient sex and endoscopic efficacy in 41 relevant studies. Increased adverse events were associated with female sex in 7 out of 14 relevant studies. CONCLUSIONS: There is no evidence for a sex difference in endoscopically measured response to biological therapies in IBD patients. However, there is an influence of sex on the occurrence of adverse events. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00384-020-03663-2) contains supplementary material, which is available to authorized users.